2019
DOI: 10.3233/blc-190251
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding Mutations in Urothelial Bladder Cancer: Biological and Clinical Relevance and Potential Utility as Biomarkers

Abstract: BACKGROUND & OBJECTIVE: Whole genome sequencing has identified recurrent non-coding mutations that may be important in carcinogenesis. We investigate the frequency of 5 such non-coding mutation hotspots in urothelial bladder cancers (UBCs) and assess their potential for UBC detection and prognostication. METHODS: DNA extracted from 302 UBCs was subjected to targeted next generation sequencing of non-coding mutation hotspots in GPR126, PLEKHS1, TBC1D12, LEPROTL1 and WDR74. The frequency of mutations, and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Building on previous studies to provide evidence for the inclusion of non-coding elements as potential biomarkers for urothelial bladder cancer (UBC) [2][3][4][5][6], Jeeta et al [1] recently identified clinically relevant non-coding mutations in five genes (TBC1D12, GPR126, PLEKHS1, LEPROTL1 and WDR74). Clinical relevance was assessed by performing analyses of mutation frequencies across disease stages, association with clinical outcomes, distribution of mutations relative to one another, relative to mutational signatures, their effects on gene expression, and isoform usage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Building on previous studies to provide evidence for the inclusion of non-coding elements as potential biomarkers for urothelial bladder cancer (UBC) [2][3][4][5][6], Jeeta et al [1] recently identified clinically relevant non-coding mutations in five genes (TBC1D12, GPR126, PLEKHS1, LEPROTL1 and WDR74). Clinical relevance was assessed by performing analyses of mutation frequencies across disease stages, association with clinical outcomes, distribution of mutations relative to one another, relative to mutational signatures, their effects on gene expression, and isoform usage.…”
mentioning
confidence: 99%
“…Substantiated by χ2 tests, logistic regression, and Cox proportional-hazards models, all of these analyses were informative. However, with regard to mutation frequencies, a more direct calculation of their cancer effect size-which accounts for underlying rates of mutation at each site and quantifies 1 (https://orcid.org/0000-0002-3548-5912) 2 (https://orcid.org/0000-0001-9306-6065) * Correspondence to: Jeffrey Townsend, Department of Biostatistics, Yale School of Public Health, 135 College Street, New Haven, CT 06510, USA. Tel.…”
mentioning
confidence: 99%
“…Notably, utDNA analysis from urine was performed without prior sequencing of tumor tissue (i.e., tumor-naive approach). We used a focused MRD gene panel encompassing 49 consensus driver genes frequently mutated in bladder cancer [ 36 40 ] ( S2 Table ). For SNV calling from urine, we utilized the CAPP-Seq with iDES pipeline [ 20 , 21 , 28 ] and filtered out any mutation also detected in the matched germline DNA sample.…”
Section: Methodsmentioning
confidence: 99%
“…Silent mutations included the following: exonic synonymous mutations, intronic mutations (except in PLEKHS1 ), promoter mutations (except in TERT ), 5′ UTR mutations (except in TBC1D12 ), and 3′ UTR mutations. Non-silent mutations included the following: exonic nonsynonymous mutations, splicing mutations, stop codon mutations, and the aforementioned exceptions based on evidence in the literature [ 28 , 36 , 38 ]. Overall utDNA levels were finally quantified as the highest variant allele fraction among non-silent mutations with duplex support detected by CAPP-Seq per urine sample.…”
Section: Methodsmentioning
confidence: 99%
“…Unpublished cohort 4 provided by Richard Bryan : RNA-Seq based analysis of 85 tumors from the West Midlands Bladder Cancer Prognosis Programme (BCPP, ethics approval 06/MRE04/65), as previously described 78 . RNA libraries were prepared using the Truseq Stranded Total RNA with Ribo-zero Gold kit (Illumina) and 2 × 100 bp PE sequenced (Hiseq, n=26) or 2 × 75 bp PE sequenced (Nextseq, n=52).…”
Section: Methodsmentioning
confidence: 99%